Sœurs de solitude : Maryse Condé et Simone Schwarz-Bart - Arzu Ildem (Études Caribéennes)
Maryse Condé and Simone Schwarz-Bart are two contemporary writers who have left a strong imprint in Caribbean Francophone literature. The two women writers are from Guadeloupe: Maryse Condé who was born in 1937 is one year older than Simone Schwarz-Bart. Maryse Condé has just received the alternative Nobel Prize for literature in 2018. Simone Schwarz-Bart wrote her first novel in collaboration with her husband André Schwarz-Bart whose novel Le Dernier des Justes was awarded the Goncourt Prize in 1959. Simone Schwarz-Bart wrote two novels herself but she has also written three novels in collaboration with her husband. The purpose of this article is to study the feeling of loneliness among the heroines of these two women writers. Their female characters have tormented lives that begin in Guadeloupe and Martinique with their births. Important moments in colonial and postcolonial history punctuate their lives that continue in a wide geography from Paris, the former metropolis, to Cape Town in South Africa. In a world emerging from slavery, only education offers the possibility of overcoming the legacy of the past. But despite their efforts, the two writers’ heroines suffer from loneliness.